Perbedaan kepercayaan diri dalam menghadapi dunia kerja antara siswa SMA dan SMK di Kabupaten Bojonegoro (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to determine self-confidence differences in dealing with the world of work between high school and vocational students in Bojonegoro Regency. The subjects of this study were students of SMAN 3 Bojonegoro and SMKN 3 Bojonegoro with the total of 150 respondents, with 75 students of each high school and vocational school. Sampling method that is used in this study is probability sampling technique using simple random sampling. The technique is used to determine the difference in self-confidence in dealing with the world of work between high school and vocational students with t-test. The results of this study gave value of “t” is equal to 0.455 and value of “p” is equal to 0.650. The empirical mean value of SMK is 86.8133 higher than the mean value of SMA is 86.0933. The results of this study indicate that there is no difference in self-confidence in facing the world of work between high school and vocational high school students. However, confidence level in facing the world of work for vocational students is higher than high school students Penelitian bertujuan untuk mengetahui apakah ada perbedaan kepercayaan diri dalam menghadapi dunia kerja antara siswa SMA dan SMK di Kabupaten Bojonegoro. Subjek penelitian ini adalah siswa SMAN 3 Bojonegoro dan SMKN 3 Bojonegoro sebanyak 150 Responden ,dengan di bagi 75 siswa SMA dan 75 siswa SMK. Pengambilan sampel dalam penelitian ini dengan menggunakan teknik probability sampling dengan menggunakan simple random sampling. Teknik yang digunakan untuk mengetahui perbedaan kepercayaan diri dalam menghadapi dunia kerja antara siswa SMA dan SMK dengan Uji-t (t-test). Hasil analisis data dengan uji-t di peroleh t= 0.455 dengan p = 0,650 Nilai Mean empiris SMK 86,8133 lebih tinggi daripada Nilai mean SMA sebesar86,0933. Hasil analisis data ini menunjukkan bahwa tidak terdapat perbedaan kepercayaan diri dalam menghadapi dunia kerja antara siswa SMA dan SMK. Kepercayaan diri dalam menghadapi dunia kerja siswa SMK lebih tinggi daripada siswa SMA.